Schooling and governance : Pedagogical knowledge and bureucratic expertise in the genesis of the Argentine educational system - Southwell, Myriam (Paedagogica historica.)
The consolidation of the Argentine Federal Government by the 1870s aimed to modernise local society, establish state institutions and reach political stabilisation. Building a modern schooling system articulated both utopia and bureaucracy by establishing the use of knowledge as an instrument of social intervention vindicating and legitimising the concept of rational control. This approach established the formal and material bases for the constitution of a field of pedagogical knowledge on one hand, and a field of bureaucratic knowledge on the other. These two fields approached the articulation of regulating devices of the educational system in distinctive ways. While normalist pedagogical knowledge involved a set of instructions on schooling, the bureaucratic knowledge of inspectors resulted in regulation of the schooling process.